PREDICTORS OF SELF‐REPORTED GAINS IN A RELATIONSHIP‐BASED HOME‐VISITING PROJECT FOR MOTHERS AFTER CHILDBIRTH. Issue 2 (20th February 2018) - Kaitz, Marsha; Chriki, Miriam; Tessler, Naomi; Levy, Judith
ABSTRACT: We assessed mothers' self‐reported gains from a postpartum home‐visiting (HV) project in which home visitors are volunteer mothers from the community. Hypotheses were that gains are positively related to (a) mothers' felt‐closeness with their home visitor, (b) mothers' level of sociodemographic risk, and (c) the home visitors' preproject training in support services for families or children (Professionalism). One hundred sixty‐four clients returned written evaluations of the HV project. Items assessing gains were reduced to two factors: Improved Well‐Being ("Self") and Improved Infant Care ("Infant"). Repeated measures general linear models, with Gains (Self, Infant) as the repeated measure, and multiple regression analyses evaluated the hypotheses. Across the sample, gains on both factors were moderate, although gain scores were higher regarding Self than for Infant. Results show that (a) Mothers' felt‐closeness with their volunteer was strongly related to mothers' gains; (b) high‐risk mothers gained more from the project than did mothers of lower risk, particularly regarding Infant Care; and (c) mothers visited by volunteers who were professionals reported more substantial gains than did mothers visited by volunteers who were not professionals. Findings can help explain variance in mothers' gains from such projects and could be useful in improving their efficacy.